Perlindungan Hukum Bagi Korban Noodweer Pada Tindak Pidana Penganiayaan Dalam Perspektif Hukum Pidana Islam (Analisis Putusan Nomor: 436/Pid.B/2024/PN.Llg) - Adelia Puspita, Andini; Hadi , Sutrisno; Sadi Is, Muhamad (Harmonization : Jurnal Ilmu Sosial, Ilmu Hukum, dan Ilmu Ekonomi, 2025)
In criminal cases, especially in the crime of persecution, there is a principle that applies that the person who commits the crime should not be punished if there is an element that eliminates the unlawful nature of the act or person, which is commonly known as the reason for criminal expungement. One of the reasons for the abolition of a criminal offense in the excuse of forgiveness is the forced defense (noodweer) which is regulated in Article 49 paragraph (1) of the Criminal Code There are two things that are raised and are the focus of this research. First, what is the basis for the judge’s consideration in deciding the punishment for the crime of persecution (Analysis of Decision Number: 436/Pid.B/2024/PN.Llg). Second, how to provide legal protection for victims of noodweer in the crime of persecution from the perspective of Islamic criminal law (Analysis of Decision Number: 436/Pid.B/2024/PN.Llg). This research method uses library research or a type of normative juridical research. The collected data is analyzed in a quantitative descriptive manner, namely by explaining regulations and analyzing a phenomenon by describing the focus of research related to the problem being studied, then conveyed inductively. The results of this study conclude that: Based on the consideration of the Panel of Judges of the Lubuklinggau District Court, the Defendant decided to impose a criminal sentence on the Defendant, therefore with a prison sentence of 1 (one) year and 2 (two) months minus the period of arrest and detention. The judge does not see that the defendant meets the noodweer requirements and can be considered legally irresponsible, the determination of noodweer as a reason for criminal expungement should be an important consideration for the judge in determining his verdict. In Islamic criminal law, noodweer is known as al-sh ’il where the law is permissible and cannot be sanctioned because this self-defense is clearly related to the purpose of (sharia maqāṣhid), namely hifdz al-Nafs or protecting the soul.